Children thermal comfort in primary schools in Ho Chi Minh City in Vietnam - Le, Thi Ho Vi; Gillott, Mark C.; Rodrigues, Lucélia Taranto (2017)
Indoor environmental quality significantly impacts on students’ performance and productivity, particularly thermal comfort levels. Currently in Vietnam, very few studies have dealt with the issue and the current trend is to install energy-intensive air-conditioning in primary schools as this is perceived as more comfortable. In this study, the authors investigated the users’ perceptions of thermal comfort in three primary schools in Ho Chi Minh City during the mid-season (September 2015) and the hottest season (April 2016). In-situ spot and long-term measurements were recorded. Questionnaires were completed by 2,145 children (from 8 to 11 years-old) and 62 teachers to understand their experiences and the extent of their interaction with the building in 62 naturally ventilated classrooms. The results were analysed by correlating the conditions measured and the comfort mean votes. Throughout this study, children were observed to tolerate higher thermal comfort condition than the recommended values in the standards. Around 7% of the occupied time during academic year presented temperatures over 33oC, in which less than 80% of the children voted acceptable. The results indicated that Vietnamese children had higher thermal comfort tolerance than the comfort levels suggested in the standards. Using air conditioning system all year round was deemed unnecessary.